Women's football: Player characteristics and demands of the game - Martinez-Lagunas, V.; Niessen, M.; Hartmann, U. (Journal of Sport and Health Science, 2014)
The number of scientific investigations on women's football specific to the topics of player characteristics and demands of the game has considerably increased in recent years due to the increased popularity of the women's game worldwide, although they are not yet as numerous as in the case of men's football. To date, only two scientific publications have attempted to review the main findings of studies published in this area. However, one of them was published about 20 years ago, when women's football was still in its infancy and there were only a few studies to report on. The other review was more recent. Nonetheless, its main focus was on the game and training demands of senior elite female players. Thus, information on female footballers of lower competitive levels and younger age groups was not included. Consequently, an updated review is needed in this area. The present article therefore aims to provide an overview of a series of studies that have been published so far on the specific characteristics of female football players and the demands of match-play. Mean values reported in the literature for age (12-27 years), body height (155-174 cm), body mass (48-72 kg), percent body fat (13%-29%), maximal oxygen uptake (45.1-55.5 mL/kg/min), Yo-Yo Intermittent Recovery Test Level 1 (780-1379 m), maximum heart rate (189-202 bpm), 30 m sprint times (4.34-4.96 s), and counter-movement jump or vertical jump (28-50 cm) vary mostly according to the players' competitive level and positional role. There are also some special considerations that coaches and other practitioners should be aware of when working with female athletes such as the menstrual cycle, potential pregnancy and lactation, common injury risks (particularly knee and head injuries) and health concerns (e.g., female athlete triad, iron deficiency, and anemia) that may affect players' football performance, health or return to play. Reported mean values for total distance covered (4-13 km), distance covered at high-speed (0.2-1.7 km), average/peak heart rate (74%-87%/94%-99% HRmax), average/peak oxygen uptake (52%-77%/96%-98% VO2max), and blood lactate (2.2-7.3 mmol/L) during women's football match-play vary according to the players' competitive level and positional role. Methodological differences may account for the discrepancy of the reported values as well. Finally, this review also aims to identify literature gaps that require further scientific research in women's football and to derive a few practical recommendations. The information presented in this report provides an objective point of reference about player characteristics and game demands at various levels of women's football, which can help coaches and sport scientists to design more effective training programs and science-based strategies for the further improvement of players' football performance, health, game standards, and positive image of this sport.